Islamic process in kazakhstan: foreign influence (Journal of Oriental Studies, 2016)
The article explores functions of foreign Muslim organizations and charity funds as one of the external factors which impacts on the Islamic process in Kazakhstan.
Keywords: Islam; Islamic revival; religious movements; Islamic organizations